(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The popularity of soccer is beyond doubt, soccer has remained one of the most popular sports in the world with a large number of active players and supporters. in today’s world, identifying and developing talented athletes in football is an important task for clubs, national federations and coaching staffs. Talent development in football is becoming increasingly relevant for researchers and practitioners. Specialists believe that one of the key aspects, which is gaining more and more importance in the process of development of young football players, is the role of social and psychological factors. Psychological state and social relationships can influence the level of motivation, self-esteem and overall success in football. The community of parents, coaches, teammates and other participants can significantly influence the development of a football player at a young age The purpose of the study is to systematize and structure the socio-psychological factors in the modern system of training young football players, which are related to the development of athletes. Research materials and methods. The main research method is the analysis of scientific and methodical literature and Internet sources, methods of information analysis and synthesis were also used. Searches were conducted using Google Scholar, a web service that allows users to search for scholarly publications, scholarly articles, books, and other scholarly sources on the Internet. A search for sources in previously published review articles was also conducted. Various combinations of keywords related to social and psychological factors in the modern system of training young football players were used. Based on the analysis of literary sources, we refined and adapted the general concept structure of the social and psychological characteristics of football players. Identified and structured characteristics that affect the further success and development of football players in the future. Based on the structuring of the analyzed data, three general groups of psychological factors are separated: psychological factors that are directly related to the athlete’s personality; external social factors related to the educational and training process in football; indicators of the behavior of the player in the team, related to the activity in the collective (team). The above framework demonstrates these psychological, social and behavioral indicators, as well as certain interrelationships between them, which contribute to the player’s career growth.